Annual Plan 1970-71 Kerala - Planning Commission (Planning Commission, 1970)
This is the largest irrigation project taken up so far in the State. the Scheme contemplates construction reservoir across the Kallada river with a storage capacity of 18,500 Mcft. the Scheme on completion benefit an area of 105218 hectares (Gross). the dam is located at Parappar.
Kerala